Legal obstacles in establishing Islamic banking in Maldives - Aishath Muneeza; Ismail Wisham (Universitas Trisakti, 2011)
Maldives is a hundred percent Muslim country. Though the laws in Maldives are influenced by common law and civil law systems, the spirit of the laws are based on Islamic principles. However, when it comcs to the banking system, it is poignant to state here that the only known banking system to the country is based on conventional or usury friendly system. Up until now there are only six banks operating in the country. And none of them is an Islamic bank. It has been frequently questioned on why it is so difficult to set up an Islamic Bank in a hundred percent Muslim country? People say that the demand is there, so what is there to worry? But the truth is that the challenges we face are more than what any one could think of. As rightly pointed out, the demand for Islamic banking is there. But what about the legal infrastructure, political support and the economic resources which are needed to invest to convert the banking system? Lack of human resources in the country is also not a small problem. And political instability has exacerbated the situation. In the past years, there have been several failed attempts made to introduce the Islamic banking system to the country. But due to lack of proper legal frame work in the country and some other financial reasons Islamic banking were never introduced. Now finally we see a green signal from the Central Bank of Maldives for establishment of Islamic bank. Towards the end of last year the Central Bank of Maldives have announced public to apply for jobs designed for the Islamic bank which is intend to be open soon! The main purpose of this paper is to look at the obstacles in introducing Islamic banking in Maldives. The challenges it is facing and the ways to curb it. It is argued here that as a Muslim nation establishment of